Detecting celiac disease in patients with Down syndrome. Issue 12 (8th September 2016) - Sharr, Christianne; Lavigne, Jenifer; Elsharkawi, Ibrahim M. A.; Ozonoff, Al; Baumer, Nicole; Brasington, Campbell; Cannon, Sheila; Crissman, Blythe; Davidson, Emily; Florez, Jose C.; Kishnani, Priya; Lombardo, Angela; et al.
Abstract : The main purposes of this undertaking were to determine how often patients with Down syndrome (DS) are screened for celiac disease (CD) across five DS specialty clinics, which symptoms of CD are most often reported to DS specialty providers at these clinics, and, how many individuals were diagnosed with CD by these clinics. This was accomplished by following 663 individuals with DS for 1 year, across five clinics in different states specializing in the comprehensive care of people with DS. Of the 663 participants, 114 individuals were screened for CD at their visit to a DS specialty clinic. Protracted constipation (43.2%) and refractory behavioral problems (23.7%) were symptoms most often reported to DS specialty providers. During the 1 year study period, 13 patients screened positive for CD by serology. Of those, eight underwent duodenal biopsy, and three were diagnosed with CD. We conclude that CD is an important consideration in the comprehensive care of individuals with DS. However, while symptoms are common, diagnoses are infrequent in DS specialty clinics. © 2016 Wiley Periodicals, Inc.